Pembuatan pemodelan sistem ground based synthetic aperture radar (GB-SAR) untuk aplikasi deteksi longsor (Making a ground based synthetic aperture radar (GB-SAR) system modeling for landslide detection applications) - Fitri Diana (Department of Physics – Universitas Negeri Padang UNP, 2016)
Ground Based Synthetic Aperture Radar (GB-SAR) is used for monitoring the displacement of landslides. Arrangement geometry of GB-SAR depend on the local topography. Calculation parameters of Synthetic Aperture Radar (SAR) system and design of tools developed need to be assessed, so that, we get the key parameters for developing the GB-SAR system matching as needed. The purpose of this research are to simulate the modeling of GB-SAR system towards the target area and resulted in the formulation of the reduction in SAR system and geometry of the illustration geometry of GB-SAR system. In general, appearance this modeling consists of two parts which are an application program and graphic modeling. GB-SAR modeling is developed based on software GUI Matlab. Variables in this research are slope hill angle, a distance of sensor to the target and bandwidth. The results of this research consists of three parts, namely the results of the formulation parameters GB-SAR geometry which are slant range center, maximum and minimum slant range, ground swath, image size, n synthetic aperture length, the next result is shape modeling GB-SAR system, and the relation between of each parameter. GB-SAR system modeling suggests that the relation between distance to the slant range and ground swath is linear proportional, while the slope hill angle is inversely proportional. In other side Relation of ground resolution with bandwidth is inversely proportional and relation ground swath with slope hill angle is linear proportional